Nutricion organica y mineral de carambola averrhoa carambola l. en la zona de Machala - Encalada Maza, Santos Tomas (2012)
The research was conducted in the farm Santa. Agnes, owned by the Faculty of Agricultural Sciences at the Technical University of Machala, located 5 km by Machala Passage. Thegoalswere. Determine the effect of organic and inorganic nutrient formulations on the yield of the fruit of carambola. Establish vegetative growth and development of plants for 180 days in the trial after fertilization. Se experiment the behavior of organic and mineral fertilizers in the planting of the crop. For the study had established the garden carambola (Averrhoa carambola) 4 years of age, organic fertilizers and chemical treatments: T1 ecoabonaza (5% N), Algreen T2, T3 Agronitrógeno (30-1, 1 + phytohormones), T4 NPK (05.05.40) and T5 control. The variables evaluated were: plant height, days to the issuance of outbreaks, number of shoots and leaves every 15 days during the trial was six months, days to flowering and fruiting from the application of treatments, number, size and weight of fruits per plant. The area corresponded to 200 m2, with 24 experimental units. From the results, we established a normal vegetative growth issuance of shoots, leaves and fruit formation in sequence in response to climate conditions and fertilization. Fruit number, size and weight increased significantly with the application of chemical fertilizer NPK based, The fruits of greater weight and size was obtained with NPK fertilizer with 9.87, 10.5 and 10.0 fruits the three crop with an average of 10.25 kilos / plant in the first. In the second crop yields remain between 7.2 kilo / plant in the control to 9.9 kilo / plant. According to these values we have that the treatment yielded better rates of productivity was the T4 treatment or application of NPK, equivalent to 30 kilos / plant.